Epidemiology of burn injury and the ideal dressing in global burn care – Regional differences explored. Issue 1 (February 2023) - Opriessnig, Elisa; Luze, Hanna; Smolle, Christian; Draschl, Alexander; Zrim, Robert; Giretzlehner, Michael; Kamolz, Lars-Peter; Nischwitz, Sebastian P.
Abstract: Purpose: Burn injuries are to this day a major cause of morbidity and mortality, especially within low- and middle-income countries. Understanding the etiology of burn injury and epidemiologic- and hospital-specific factors associated with burns is vital for allotting resources for prevention and treatment. Therefore, the purpose of this study was to develop a profile of epidemiological differences in burn care and the ideal burn dressing among the different continents based on a global online survey. Objectives: This analysis evaluated trends in demographics, epidemiology of burn care, burn incidence, infection, related mortality and burn treatment (e.g., dressing changes and materials). The objective of this study was to investigate and compare the epidemiological profile of burn injury/care amongst the continents and a global control group to determine their utility for guiding evidence-based burn care and identify differences and/or similarities in their clinical practice. Methods: A retrospective analysis of data was performed that was acquired during a previous study investigating the ideal burn dressing on a global perspective. The data was analyzed depending on the continent, on which the respondent indicated their hospital to be (Africa, Australia & New Zealand, Asia, Europe, Middle and South America, North America). Statistical analysis was performed to evaluate patient and hospital demographics and variables associated with burn injuries and their treatment. Outcomes of interest also included infections, mortality, length of stay on the ICU and important burn dressing characteristics. Results: Healthcare providers in different areas of the world share similar views and needs regarding burn care management and on what constitutes an ideal burn dressing. We found significant differences in the various continents regarding hospitalization and length of stay on the ICU, with Australia taking the lead. Africa, with a high proportion of low-income-countries, reported the highest rate of burn infections, mortality, and a disproportionally high number of burn incidences amongst children. In general, men were mostly obtaining burn injuries amongst all continents. We found no significant differences regarding the most important characteristics of an ideal burn dressing. Conclusion: Our results suggest significant epidemiological differences regarding burn injuries and care amongst the continents, possibly resulting from the different infrastructure and/or circumstances on the various continents. Future scientific studies need to focus on adequate pain management and designing longer lasting materials that contain the "ideal" properties, by also taking individual regional needs/desires and the patient's perspective and economic boundaries into account. This analysis has delivered valuable insights into the epidemiological differences and/or similarities amongst the various continents. Highlights: Burn care is vital on a global scale, however, priorities differ in different regions. Pain reduction, anti-infectiveness, pain-free dressing changes are of high importance. The choice of burn dressing can significantly influence the outcome of burn injury. Men were mostly obtaining burn injuries amongst all continents. Hospitalization and Length of hospital stay (ICU) differ amongst all continents. Africa reports the highest rate of burn infections.